IDENTIFIKASI KERAGAMAN FENOTIP KARAKTER KUALITATIF DAN KUANTITATIF KELAPA SAWIT (Elaeis guineensis Jacq.) ASAL ANGOLA - Achmad Fathoni; Siti Zahrah; Fathurrahman (Ekoagrotrop, 2023)
The research entitled identification the phenotypic variance of qualitative and quantitative characters of oil palm (Elaeis guineensis Jacq.) origin of Angola. The objective of the study was to determine the specific characteristics of the oil palm population of dura and tenera Angolan germplasm on phenotypical characterization whether qualitatively and quantitatively as well. The research was conducted in seeds garden of the oil palm seeds company in Siak Hulu of Kampar District. The genetic material used in this study was oil palm germplasm as much as 1996 oil palms in 15.50 hectars. The Angola accession population consisted of 80 Dura accessions with 1,309 oil palms and 26 Tenera Accessions with 687 oil palms. The analytical method used is the Coefficient of Phenotypic Variation (KKF) and Principal Component Analysis (PCA). The results show that the main component of the quantitative variable can explain the variation of the Angolan oil palm population by 79.76% with parameters such as oil to bunch (%), oil to fruit (%), dry mesocarpto fruit (%), relative leaf area (m²), wet mesocarp to fruit, frond length, palm height, number of leaves, periole width (cm), and petiole cross-section (cm²). The proportion of low KKF with a high O/B average is found in AGO001, AGO086, AGO101, and AGO 106.